Managing negative people : strategies for success - Kravitz, S. Michael (Crisp Pub. Menlo ParkUS, 1995)
Provides an understanding of negative people as well as techniques for dealing with and overcoming negativity, both personally, and in others. Suggests an action plan for 'building positivity muscles'.